Over-expression of lysine-specific demethylase 1 predicts tumor progression and poor prognosis in human esophageal cancer - Chen, Lujun (Int J Clin Exp Pathol, 2014)
Lysine specific demethylase 1 (LSD1), the first characterized histone demethylase, roles importantly in epigenetic regulation of carcinogenesis and cancer progression. In the present study, we examined LSD1 expression in 103 cases of esophageal cancer tissues, and further investigated its relationship to patient’s clinical parameters and post-operative prognosis. We found that the positive LSD1 immunochemical staining was predominantly observed on the nuclei and cytoplasm of esophageal cancer cells, while negative or very weak in adjacent normal tissues. The intensity of LSD1 immunostaining was significantly correlated to the tumor size (P = 0.013), nodal metastasis (P = 0.002), distant metastasis (P = 0.025), and TNM stage (P = 0.010), whereas it was not correlated to patient’s gender, age and tumor invasion depth. The overall survival rate of patients with low LSD1 expression was better than those with high LSD1 expression (P = 0.014). We also showed that the tumor size (P = 0.003) as well as the TNM stage (P = 0.007) was a useful prognostic predictor for esophageal cancer. However, when the gender, age, tumor size, TNM stage and LSD1 expression level were involved in the multivariate proportional hazards regression analysis in a Cox’s model, we showed that the tumor size (P = 0.013) and the TNM stage (P = 0.032) could be used as independent risk factors to predict patient’s postoperative prognosis, but LSD1 expression level as well as other factors could not independently predict patient’s outcome. Thus, our results indicated that LSD1 was involved in cancer progression and metastasis in human esophageal cancer, and could be a potential prognostic predictor for this malignancy.